Speciation Analysis of Cadmium in Dust Fall About Northern China Towns - Wang, Min; Deng, Yue-Quan; Dong, Fa-Qin; He, Xiao-Chun; Dai, Qun-Wei; Sun, Shi-Yong; Huang, Yun-Bi; Tang, Jun; Chen, Wu; Liu, Li-Zhu; et al. (Asian Journal of Chemistry, 2013)
In this article, the determination of the speciation of cadmium in dustfall about Northern China towns with reliable analytical method is reported. The distribution of total Cd varies in different regions, among which Duoba town of Qinghai Province tops it with the Cd amount of 5.3921 μg/g. And that of Shuangta town, Hebei Province is 2.0256 μg/g and the rest distribution are rather low, with the distribution 0.6-1.5 μg/g. Seeing from the Cd's average content level, these speciations' percentage are as follows: exchangeable form of 0.1484 μg/g, carbonates of 0.2283 μg/g, organic combination of 0.1750 μg/g and residual of 0.9179 μg/g. Besides, mainly form is residual and of low Fe-Mn oxides.